Assessing business zakat at Pusat Zakat Selangor: between theory and practice / Rashidah Abdul Rahman and Rohila Awang - Abdul Rahman, Rashidah; Awang, Rohila (Faculty of Accountancy, 2003)
The main objective of this study is to determine the value measurement used by zakat collection centres, particularly Pusat Zakat Selangor (PZS), in measuring business zakat among companies owned by Muslims in Selangor territory. The study found that PZS assessed zakat from companies financial statements based on historical cost, and not current value as hypothesised by previous researches. The continuous use of historical cost may lead to negative wealth transfer for zakat beneficiaries particularly in time of rising prices. Even though certain adjustments are made to the assessment, however the purpose of such adjustment is merely to reflect the Islamic philosophy of the implementation of halal and haram as well as different views of Islamic Accounting and Conventional Accounting in recognising income and expenses.